Adaptação transcultural e validação do instrumento Patient Engagement in Patient Safety within Canadian Healthcare Organizations para uso no Brasil - Sousa, Maiana Regina Gomes de (2022)
INTRODUCTION: for more than two decades, patient safety has been highlighted as a global health challenge, requiring changes and implementation of initiatives to minimize risks, prevent care failures and prevent harm to patients. Patient engagement in patient safety has been one of the strategies used in the main international recommendations to improve the quality and safety of care, making relevant the existence of instruments to evaluate this practice. OBJECTIVE: to produce the Brazilian version of the instrument Patient Engagement in Patient Safety within Canadian Healthcare Organizations. METHOD: methodological study involving cross-cultural adaptation and validation of the instrument Patient Engagement in Patient Safety within Canadian Healthcare Organizations for use in Brazil, developed in two phases. The first phase, held between January 2020 and June 2021, consisted of the cross-cultural adaptation of the instrument for the Portuguese Brazilian and followed six steps: preparation, translation, back translation, pretest with nine health organizations, review, and documentation. The second phase, held between August and November 2021, was to validate of the content of the instrument using the Delphi technique, through the evaluation of a committee of experts in two sequential rounds. The semantic, conceptual, and normative equivalence of the items of the instrument were analyzed using the Coefficient of Agreement between evaluators, being considered satisfactory values greater than or equal to 90.0%. To analyze the content validity was used the Content Validity Index (CVI) and Inter-Rater Agreement (IRA), being considered approved values greater than 0.8, for both CVI and IRA. The analyses were performed using the Software R version 4.1.2. RESULTS: in cross-cultural adaptation, 97.9% of the items of the instrument were considered equivalent by 100% of the evaluators. For the items that presented agreement less than 90%, the best solutions were discussed, until a consensus was reached. The modifications made were approved by the authors of the original instrument. In content validation, most items had CVI approved in all three aspects, with 99.3% for coverage, 95.8% for clarity and 96.1% for relevance. About the IRA, 99.0% of the items presented satisfactory values for coverage, clarity, and relevance. Items with unsatisfactory values were changed and evaluated again by the expert committee and after approval by all the instrument was concluded, available for use in Brazil with the title “Engajamento do Pacientes na Segurança do Paciente em Organizações de Saúde”. CONCLUSION: the instrument is a reliable and valid tool to investigate patient engagement strategies in patient safety implemented in Brazilian health organizations, at different levels of governance.